2007
DOI: 10.1146/annurev.immunol.25.022106.141557
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Family Cytokines and the Expanding Diversity of Effector T Cell Lineages

Abstract: Since its conception two decades ago, the Th1-Th2 paradigm has provided a framework for understanding T cell biology and the interplay of innate and adaptive immunity. Naive T cells differentiate into effector T cells with enhanced functional potential for orchestrating pathogen clearance largely under the guidance of cytokines produced by cells of the innate immune system that have been activated by recognition of those pathogens. This secondary education of post-thymic T cells provides a mechanism for approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

39
1,456
2
31

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,674 publications
(1,528 citation statements)
references
References 134 publications
39
1,456
2
31
Order By: Relevance
“…Therefore, we hypothesized a role of TLR2-expressing LC for polarizing Th17 immune responses and investigated their potential to induce IL-17. In this study we show that peptidoglycan (PGN)-stimulated MoLC secreted IL-6, IL-1b, IL-23, and TGF-b Blocking of TLR2 by specific antibody inhibited IL-6, IL- To date, IL-6 and TGF-b are prominent cytokine candidates for polarization of naive Th cells into Th17 cells, whereas IL-23 is discussed for Th17 outgrowth of already differentiated cells [5][6][7]26]. In human skin, among other cytokines IL-6 is produced by LC upon microbial stimulation by PGN and other TLR2 agonists [23].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, we hypothesized a role of TLR2-expressing LC for polarizing Th17 immune responses and investigated their potential to induce IL-17. In this study we show that peptidoglycan (PGN)-stimulated MoLC secreted IL-6, IL-1b, IL-23, and TGF-b Blocking of TLR2 by specific antibody inhibited IL-6, IL- To date, IL-6 and TGF-b are prominent cytokine candidates for polarization of naive Th cells into Th17 cells, whereas IL-23 is discussed for Th17 outgrowth of already differentiated cells [5][6][7]26]. In human skin, among other cytokines IL-6 is produced by LC upon microbial stimulation by PGN and other TLR2 agonists [23].…”
Section: Introductionmentioning
confidence: 82%
“…Upon stimulation Th17 cells acquire the capacity to produce the inflammatory cytokine IL-17 [4]. Recent reports demonstrate that Th17 cells are involved in processes of defence against extracellular bacteria and fungi, cancer and autoimmunity [5][6][7]. Furthermore, it was observed that the Th2-derived IL-17E, which is a member of the IL-17 cytokine family (A-F), plays a role in boosting allergic reactions by induction of IL-4, IL-5, and IL-13.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Interestingly, Th17-related cytokines such as IL-17, IL-6 and GM-CSF [12,29], were also significantly higher in IL-10 À/À mice, when compared with WT control animals, indicating that IL-10 À/À mice not only develop a Th1 immune response, but also an antigen-specific Th17 response after T. muris infection (Fig. 1A).…”
mentioning
confidence: 94%
“…The Th2 immune response with T cells producing IL-4, IL-5 and IL-13 provides immunity to helminths [2]. Th17 cells produce cytokines like IL-17, IL-22 and mediate immunity to extracellular bacteria and fungi, but are also responsible for autoimmunity and inflammation [12,13]. Development of naïve T cells to Th17 cells requires the presence of IL-6, TGF-b1 and the transcription factor RORgt [14][15][16][17].…”
mentioning
confidence: 99%
“…In Th17 cell development, native CD4 þ T cells are activated by IL-6 from mature dendritic cells, which acts together with activated TGF-b to induce expression of the retinoic orphan receptor RORgt and upregulate IL-23R, thus making them competent for IL-17 production through STAT 3 signalling. 6,7 The importance of IL-23R in controlling innate immunity through Th17 cells may underscore why the IL23R gene also has been demonstrated to confer susceptibility to several autoimmune diseases, including psoriasis, 8,9 ankylosing spondylitis, 10 multiple sclerosis [11][12][13] and inflammatory bowel diseases (both Crohn's disease and/or ulcerative colitis). 14,15 In addition, a separate study by the Wellcome Trust Case Control Consortium and the Australo-Anglo-American Spondylitis Consortium found evidence to suggest that IL23R may be a common susceptibility factor for the major 'seronegative' diseases.…”
Section: Introductionmentioning
confidence: 99%